2019
DOI: 10.1007/s10549-019-05412-8
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of radiotherapy after breast-conserving surgery in older patients with T1-2N0 breast cancer

Abstract: Purpose In the Netherlands, radiotherapy after breast-conserving surgery (BCS) is omitted in up to 30% of patients aged ≥ 75 years. Although omission of radiotherapy is considered an option for older women treated with endocrine treatment, the majority of these patients do not receive systemic treatment following Dutch treatment guidelines. Therefore, the aim of this study was to evaluate the effect of omission of radiotherapy on locoregional recurrence risk in this patient population. Methods Patients aged ≥ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Swallowing complaints/oesophagus regional Swallowing complaints/in case of regional RT Other Changes in the effects if also chemotherapy given information should be communicated varied between all interviewed persons. Although in some countries endocrine therapy is offered to patients with a very low risk of recurrence, affecting the balance on advantages and disadvantages of choosing for RT and/or endocrine therapy this is not clinical practice in the Netherlands [3] and was therefore not included in this study.…”
Section: Reduced Arm Mobilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Swallowing complaints/oesophagus regional Swallowing complaints/in case of regional RT Other Changes in the effects if also chemotherapy given information should be communicated varied between all interviewed persons. Although in some countries endocrine therapy is offered to patients with a very low risk of recurrence, affecting the balance on advantages and disadvantages of choosing for RT and/or endocrine therapy this is not clinical practice in the Netherlands [3] and was therefore not included in this study.…”
Section: Reduced Arm Mobilitymentioning
confidence: 99%
“…Clinical trials, such as the PRIME II trial [1], the BASO II trial [2], and the EUROPA trial (NCT04134598), evaluate the omission and/or replacement of endocrine therapy with breast radiotherapy (RT) for these patients. In the Netherlands, where endocrine therapy is not offered for these very low risk invasive breast cancer, the TOP-1 trial is being conducted in which also the local breast RT is omitted after breast conserving surgery in patients above 70 years of age (NL5983) [1,3].…”
Section: Introductionmentioning
confidence: 99%
“…Also Kunkler et al stated, that the 5-year ipsilateral breast tumor recurrence rate is probably low enough for women older than 65 years to forgo radiotherapy after BCS [7]. De Boer et al recently showed that recurrence risk in elderly patients aged � 75 years with T1-2N0 breast cancer was low, even without radiotherapy [33].…”
Section: Plos Onementioning
confidence: 99%
“…All the studies in the present review included patients who were using different therapies such as surgery, chemotherapy, radiotherapy, hormonal/endocrine therapy, adjuvant therapy, neoadjuvant therapy. Surgery was the primary method of treating BC in most of the studies [56,57,60,62,[64][65][66]. While a single study reported patients using adjuvant and neoadjuvant therapy [54].…”
Section: Treatmentmentioning
confidence: 99%